2016
DOI: 10.1016/j.jcrysgro.2016.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of the horizontal ribbon growth process

Abstract: Experimental and numerical results are presented on the process of horizontal ribbon growth (HRG) of single-crystal silicon. Experimental data on the leading edge position of the growth front as a function of pull speed is compared to model predictions with and without solidification kinetic effects. Without kinetics, the numerical results predict leading edge positions which are completely different than that observed in the experiment. With kinetics, the leading edge position is predicted typically within 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…9, which also shows an initial element mesh used for the calculations. In [1], we showed that the model predictions of the location of the triple junction, x tj , as a function of pull speed agree well with that seen in the experiment. Fig.…”
Section: Application To Horizontal Ribbon Growthsupporting
confidence: 76%
See 2 more Smart Citations
“…9, which also shows an initial element mesh used for the calculations. In [1], we showed that the model predictions of the location of the triple junction, x tj , as a function of pull speed agree well with that seen in the experiment. Fig.…”
Section: Application To Horizontal Ribbon Growthsupporting
confidence: 76%
“…Previous studies of horizontal ribbon growth did not consider these effects [3][4][5][6][7][8][9][10][11][12][13][14]. In [1], it was shown that facet kinetics limit the maximum growth rate attainable by FSM. This limitation manifested itself in the numerical results as a turning point in the response of the growth front position versus the pull speed; beyond a limiting pull speed no steady solutions could be found.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The liquid emissivity, ε l , equal to 0.2 and the solid emissivity, ε s , equal to 0.6. 15 In this case, the radiation heat flux function can be approximated as:…”
Section: Thermal Boundary Conditionsmentioning
confidence: 99%
“…In the last 10 years, other new liquid crystallization options have arisen, undaunted by the market dominance of Czochralski (Cz) and multicrystalline (mc) ingot growth. Cast monocrystalline, Direct Wafer, low‐angle sheet silicon, and mushroom‐shaped crucible growth have each demonstrated promise in quality and/or silicon utilization, although none has broken through to large‐scale production. Meanwhile, the 2 big contenders, Czochralski pulling and multicrystalline casting, have seen tremendous amounts of continuous improvement and have grown to an enormous scale without a clear winner emerging .…”
Section: Introductionmentioning
confidence: 99%